2007
DOI: 10.1111/j.1467-9930.2007.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Magistrates, Magistrates Courts, and Social Change

Abstract: Relatively little attention has been paid to lower courts' capacity to bring about social change, despite the fact that most citizens who come into contact with the judicial system will have their case considered (and most likely only considered) by these courts. Often these citizens experience a range of problems that are social in origin, including precarious employment, welfare dependence, financial hardship, and various health problems, including mental health and drug dependency. Magistrates courts must r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In the same way that Cowan et al observed something of a deficit in socio-legal work on the lower courts, Anleu and Mack (2007) recognise that much of socio-legal literature has tended to focus on the procedures and decisions of the higher courts (as an illustration of this point, at page 183, they cite the work of Anleu, 2000;Barnett, 1993;Brigham, 1996;Hambly and Goldring, 1976;Rosenberg, 1993;Solomon, 1992;Vago, 2003). This, they argue, is unfortunate, given that:…”
Section: Socio-legal Studies Of the Mechanism Of Law Legal Procedurementioning
confidence: 84%
“…In the same way that Cowan et al observed something of a deficit in socio-legal work on the lower courts, Anleu and Mack (2007) recognise that much of socio-legal literature has tended to focus on the procedures and decisions of the higher courts (as an illustration of this point, at page 183, they cite the work of Anleu, 2000;Barnett, 1993;Brigham, 1996;Hambly and Goldring, 1976;Rosenberg, 1993;Solomon, 1992;Vago, 2003). This, they argue, is unfortunate, given that:…”
Section: Socio-legal Studies Of the Mechanism Of Law Legal Procedurementioning
confidence: 84%
“…In Brazil, as in other countries, judges are heavily influenced by official and professional prescriptions. The range of social expectations about judicial work and judges' behavior extends along a spectrum from strict compliance and application of law to social activism (Roach Anleu and Mack 2007). Various theories and approaches are positioned between these two poles and can be used in seeking to explain the behavior of judges.…”
Section: Role Theory and Judicial Behaviormentioning
confidence: 99%
“…All of these facets of geography have performative aspects, as well as having representative force and material life. Law and legal systems are similarly broad, including the performed (for example of the nation state, see Weber, 1998; for example of property, see Blomley, 2013) as well as the representational and material products of rule-based systems intended to regulate human behaviour (see for example Moore, 1973;Anleu, 2000). Any study of the law also necessarily incorporates what is made illegal as well as what is sanctioned as legal, and sources of informal as well as formal control (see for example Hall, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, legal geography includes what has traditionally lain beyond the scope of the discipline of law. Law is largely studied in the abstract, ignoring both its spatial and social contexts (see for example Moore, 1973;Posner, 1987;Anleu, 2000). Legal geography addresses this 'legal closure', the solipsistic claim the law makes for its separateness and supremacy, in order to understand laws as embedded in (co-constituted) social and political life that is in turn emplaced (Blomley, 1994;Delaney, 2010).…”
Section: Introductionmentioning
confidence: 99%